Elementary science teaching: Actions, dispositions, and decisions that shape learning - Bhutta, Sadia Muzaffar; Ahmed, Afaq; Ahmad, Sohail; Ansari, Aisha Naz (American Journal of STEM Education, 2026)
Instructional decision-making process is inherently complex, involving reasoning, choices, and dispositions that shape classroom practices. Science teachers’ pedagogical actions and decisions are influenced by multiple factors, ranging from intrinsic beliefs to external constraints. This study explores the interplay of actions, dispositions, and decision-making in various teaching and learning strategies used in science classrooms. Using classroom observations and semi-structured interviews with 16 elementary science teachers from a nationwide mixed-methods study, we examine their instructional approaches. Findings indicate that most teachers rely on traditional methods, such as ‘chalk-and-talk’ or text-based instruction, with their pedagogical strategies being predominantly discipline-oriented. Teachers' narratives reveal gaps in pedagogical knowledge, often leading to misconceptions or inadequate instructional dispositions. Drawing on situated cognition theory, we discuss how internal factors, including exam-driven teaching and workplace conditions, shape science instruction. Based on these findings, we propose recommendations to enhance science teaching practices.